THE EFFECTIVENESS OF THE KANBAN METHOD IN DEVELOPING ACCOUNTING INFORMATION SYSTEMS FOR MSMEs - Andhika Anandya; Rini Lestari; Rudy Hartanto; Edi Sukarmanto; Asri Suangga; Lukmannul Hakim Firdaus (UPT Publikasi Ilmiah UNISBA, 2023)
This research analyzes the effectiveness of implementing the Kanban Method in developing a simple accounting information system for MSMEs in Bandung, particularly those under the guidance of PC Persis Banjaran. The study employs a qualitative approach with a triangulation method, which combines data from direct observations and interviews with system developers, business actors as prospective system users, and experts, as well as the analysis of relevant documents. The research findings demonstrate that the application of the Kanban Method in developing accounting information systems is quite effective. The Kanban Method enables system developers to become more adaptive and responsive in addressing changes in the development needs of information systems. This study reveals that the use of the Kanban Method in developing a simple accounting information system leads to improvements in data processing effectiveness, financial transaction calculations, and zakat reporting according to the needs of prospective system users. Keywords : Kanban, Accounting information system, MSMEs, Bandung, PC Persis Banjaran.